The Church in the Public Space: Lessons from the Exodus Church in Jürgen Moltmann’s Theology of Hope - Osei, Isaac Karkari; Obimpeh-Quayson, Emmanuel (Universitas Pelita Harapan, 2024)
The ecclesial community's call to duty and ability to carry out its mission is centered on how relevant it must become to the existential realities of those living in the public sphere. Jürgen Moltmann makes what can only be considered as a concise statement when he states that, to make Christianity accessible to the masses, theology must openly uphold the universal concerns of God's coming Kingdom. The church, following its own faith principles, must demonstrate